Pengaruh Pemakaian Ethyl Chloride Spray Terhadap Tingkat Nyeri Pada Pasien Hemodialisis Dengan Insersi Fistula Arterio Venous Di Klinik Utama Bali Husada Cipta Chanti - Ni Kadek Lisyawati; I Putu Artha Wijaya; A.A. Kompiang Ngurah Darmawan (Poltekkes Kemenkes Malang, 2020)
Hemodialysis is one of the therapies for patients with chronic kidney failure in the form of the process of cleaning blood from metabolic products that are no longer needed by the body by filtering that is done outside the human body, using a dialysis machine as a kidney replacement known as renal replacement therapy. Hemodialysis requires the access of the hemodialysis machine to connect with the patients blood vessels so that the insertion of the fistula in the arteries and veins in each action and cause pain. One way to reduce the level of pain during fistula insertion is by spraying ethyl chloride spray in the area of the arteries and veins to be carried out fistula insertion. The purpose of this study was to determine the effect of using ethyl chloride spray on pain levels in hemodialysis patients with fistula insertion of arterio venous at the Main Clinic of Bali Husada Cipta Chanti. This research method uses pre experiment with the one group pre test post test design. The sampling technique used was simple random sampling without replacement with a total sample of 69 respondents. The instrument used to measure the level of pain is the Numerical Rating Scale. The research data were analyzed with Wilcoxon signed rank test with p value is 0,000, so that it can be concluded that there is an effect of using ethyl chloride spray on pain levels in hemodialysis patients with insertion fistula in arterio venous at Main Clinic Bali Husada Cipta Chanti.